Gradient wettability self-cleaning nano paper as well as preparation and application thereof

By using amphiphilic lignin nanoparticles as bridge particles and modified cellulose as substrate in Janus nanopaper, a light-induced anti-fouling Janus film was prepared, which solved the problems of poor adhesion, low flux and membrane pollution between the Janus nanopapers in the prior art, and achieved efficient oil-water separation.

CN119824712AActive Publication Date: 2025-04-15GUANGXI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411881555.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-15
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing Janus nanopaper has poor interlayer adhesion, low flux and membrane pollution problems, resulting in low oil-water separation efficiency and flux.

Method used

Using amphiphilic lignin nanoparticles (LNPs) with spherical topology as the bridge particles and modified multi-scale cellulose as the heterogeneous substrate, a light-induced anti-fouling Janus film with microchannel stability was prepared through the particle bridging strategy.

Benefits of technology

The efficient separation of heavy oil-water emulsion was achieved, with the separation efficiency reaching 99.7% and 98.1%, the flux reached 100 times that of commercial nanofiltration membranes, and the efficient separation performance was still maintained after ten cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824712A_ABST
    Figure CN119824712A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of wood fiber biomass high-value utilization, in particular to gradient wettability self-cleaning nano paper and preparation and application thereof. In order to solve the problems of poor interlayer adhesion, low flux, membrane pollution and the like of Janus nanopaper, amphiphilic lignin nanoparticles (LNPs) with a spherical topological structure are adopted as bridging particles, modified multi-scale cellulose is adopted as a heterogeneous substrate, and the photoinduced antifouling Janus membrane with microchannel stability is prepared through a particle bridging strategy. The heavy oil-water emulsion can be quickly and efficiently separated. Stable high-flux separation of the water-in-heavy oil emulsion (O / W) and the water-in-heavy oil emulsion (W / O) is achieved, the separation efficiency reaches up to 99.7% and 98.1% respectively, and the flux is 6298 L * m <-2 > * h <-1 > * bar <-1 > and 5499 L * m <-2 > * h <-1 > * bar <-1 > respectively. The flux is 100 times that of a commercially available nanofiltration membrane. And excellent separation flux can still be maintained after ten times of circulation. The research provides a new strategy for treating complex oil spilling wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of high-value utilization of wood fiber biomass, and specifically to a gradient wettability self-cleaning nanopaper and its preparation and application. Background Art

[0002] The oil spill problem is an international environmental challenge. Oily wastewater contains high concentrations of petroleum hydrocarbons and other toxic and hazardous substances. It seriously threatens marine ecology and human safety. Janus membrane separation technology is a promising solution with high separation efficiency, low energy consumption, high cost-effectiveness, and is suitable for a variety of industrial wastewaters, making it attractive in demulsification. Compared with traditional single-phase permeation membranes, Janus membranes have an asymmetric structure that can integrate multiple functional components into one unit, resulting in additional anisotropic derivative properties and functions. However, the separation flux is still limited by the micropore porosity and layer structure bridging stability. On the one hand, in the actual preparation process, the porosity of the open microchannel decreases, which in turn leads to a decrease in separation efficiency. On the other hand, due to the weak bonding ability of the hydrophobic layer and the hydrophilic layer of the separation membrane. Therefore, designing a fiber-based asymmetric wettability Janus membrane with super wettability, adjustable pores and stable interlayer structure is the key to achieve high flux and efficient selective separation of oil and water.

[0003] Therefore, finding a method that can solve the problems of poor interlayer adhesion, low flux and membrane fouling of Janus nanopaper is the current key research direction. Summary of the invention

[0004] In order to solve the above technical problems existing in the prior art, the present application provides a gradient wettability self-cleaning nanopaper and its preparation and application.

[0005] A method for preparing gradient wettability self-cleaning nanopaper specifically comprises the following steps:

[0006] (1) Preparation of nanocellulose (CNF): Poplar wood cellulose with a moisture content of 20-30 wt% was ground and then homogenized to obtain 2 wt% nanocellulose;

[0007] (2) anionizing the CNF prepared in step (1) through a tetramethylpiperidinyl oxide (TEMPO)-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF); this step is to convert the primary hydroxyl groups in CNF into carboxyl groups;

[0008] (3) Preparation of hydrophobic fiber layer: Take the TOCNF obtained in step (2) and prepare 1-3 mg·mL -1 dispersion, add EDS and NHS; stir to activate; add 2-10 mg·mL -1ODA was reacted; after the reaction, a hydrophobic cellulose derivative (ODANF) was obtained;

[0009] (4) Preparation of hydrophilic fiber layer: Take the TOCNF obtained in step (2) as raw material and prepare 2 mg mL -1 The dispersion was added with EDS and NH; stirred for activation; AZO was added for reaction; after the reaction, a photoresponsive cellulose derivative (AZONF) was obtained;

[0010] (5) Preparation of lignin nanoparticles (LNPs): Dissolve lignin in tetrahydrofuran to obtain a concentration of 2-10 mg mL -1 The original solution of lignin; at 300-800rmp·min -1 At a rotation speed of , the original lignin solution is slowly added dropwise into ultrapure water; magnetic stirring is applied, and lignin nanoparticles are obtained after THF evaporates;

[0011] (6) Assembly of Janus nanopaper: ODANF, AZONF and LNPs obtained in steps (3), (4) and (5) were set aside and assembled layer by layer in the order of ODANF, LNPs and AZONF using a vacuum filtration method to prepare Janus nanopaper with asymmetric wettability.

[0012] Furthermore, the step (1) is to grind the poplar cellulose with a moisture content of 25 wt% using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC); and after a homogenization process, 2 wt% nanocellulose is obtained.

[0013] Furthermore, in step (2) and step (3), the molar ratio of EDS and NHS added is (1:1).

[0014] Furthermore, the stirring activation in step (2) and step (3) is to activate cellulose for 1 hour under magnetic stirring at 500 rpm.

[0015] Furthermore, in step (3), 2-10 mg·mL is added -1 The reaction was carried out with ODA at 60°C for 5h.

[0016] Furthermore, the step (4) of adding AZO to react is to add 0.1-0.9 mg·mL -1 The AZO was reacted at 60 °C for 5 h.

[0017] Furthermore, the step (5) is to dissolve 20-100 mg of lignin in 10 mL of tetrahydrofuran to obtain a concentration of 2-10 mg mL -1The original lignin solution; at 500rmp·min -1 The original lignin solution was slowly added dropwise into 30 mL of ultrapure water at a rotation speed of ; magnetic stirring was performed for 24 h, and lignin nanoparticles were obtained after THF evaporated.

[0018] Furthermore, the step (6) is specifically as follows: first, 10 ml of AZONF dispersion (0.2 wt%) is filtered through a PTFE polytetrafluoroethylene microporous membrane; then, 0.5 mg·mL-1 of LNPs is deposited on top of AZONF; finally, 20 mL of ODANF suspension (0.1 wt%) is deposited on top of LNP; after drying at 40°C for 12 h, a wettability gradient composite membrane (JA / O@LNP) is obtained; wherein the hydrophobic layer is denoted as the JO layer, and the hydrophilic layer is denoted as the JA layer.

[0019] A gradient wettability self-cleaning nanopaper is prepared by the method.

[0020] The gradient wettability self-cleaning nanopaper is used in oil-water separation.

[0021] Compared with the prior art, the technical effects created by this application are embodied in:

[0022] This scheme aims to solve the problems of poor interlayer adhesion, low flux and membrane fouling of Janus nanopaper. Amphiphilic lignin nanoparticles (LNPs) with spherical topology are used as bridging particles, and modified multi-scale cellulose is used as a heterogeneous substrate. Through the particle bridging strategy, a light-induced antifouling Janus membrane with microchannel stability is prepared, which can quickly and efficiently separate heavy oil-water emulsions. Stable high-throughput separation of heavy oil-water emulsion (O / W) and heavy oil-water emulsion (W / O) is achieved, with separation efficiencies of 99.7% and 98.1%, respectively, and fluxes of 6298 L×m -2 ×h -1 ×bar -1 and 5499L×m -2 ×h -1 ×bar -1 The flux is 100 times that of commercially available nanofiltration membranes. Excellent separation flux can still be maintained after ten cycles. This study provides a new strategy for treating complex oil spill wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the cross section of the Janus nanopaper prepared in Example 1.

[0024] Figure 2 It is a scanning electron microscope image and a physical image of the cross section of the hydrophilic JA layer of the Janus nanopaper prepared in Example 1.

[0025] Figure 3 It is a scanning electron microscope image and a physical image of the cross section of the hydrophobic JO layer of the Janus nanopaper prepared in Example 1.

[0026] Figure 4 This is a transmission electron micrograph of the lignin nanoparticles prepared in Example 1.

[0027] Figure 5 This is a physical CT scan image of the Janus nanopaper prepared in Example 1.

[0028] Figure 6 It is a comparison chart of the light oil-water mixture separation efficiency and flux of Example 1 and Comparative Examples 1 and 2.

[0029] Figure 7 It is a comparison chart of the separation efficiency and flux of the heavy oil-water mixture of Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0030] The technical solution of the present application is further limited below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0031] Example 1

[0032] The present invention provides a method for preparing gradient wettability self-cleaning nanopaper for oil-water separation. The invention uses amphiphilic lignin nanoparticles (LNPs) with a spherical topological structure as bridging particles and modified multi-scale cellulose as a heterogeneous substrate. A "hydrophilic-amphiphilic-hydrophobic" longitudinal fluid directional transport structure is formed under interfacial interaction. A light-induced antifouling Janus nanopaper with microchannel stability is prepared by a particle bridging strategy for oil-water separation.

[0033] The present invention relates to a method for preparing gradient wettability self-cleaning Janus nanopaper for oil-water separation, and the specific implementation process is as follows:

[0034] (1) Poplar cellulose with a moisture content of 25 wt% was ground using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC). After homogenization, 2 wt% nanocellulose (CNF) was obtained. CNF was anionized by TEMPO-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF).

[0035] (2) Preparation of hydrophobic fiber layer: 2 mg mL -1 EDS and NHS were added to the TOCNF dispersion at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 4 mg mL -1The ODA was reacted at 60°C for 5 h. After the reaction, a hydrophobic cellulose derivative (ODANF) was obtained.

[0036] (3) Preparation of hydrophilic fiber layer: 2 mg mL -1 TOCNF was used as raw material, and EDS and NHS were added at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 0.3 mg mL -1 The AZO was reacted at 60°C for 5 h. After the reaction, a photoresponsive cellulose derivative (AZONF) was obtained.

[0037] (4) Preparation of lignin nanoparticles (LNPs): 40 mg of lignin was dissolved in 10 mL of tetrahydrofuran to obtain a concentration of 4 mg mL -1 The original lignin solution. At 500rmp·min -1 The original lignin solution was slowly added dropwise to 30 mL of ultrapure water at a rotation speed of 1.5 %. The mixture was stirred magnetically for 24 h, and lignin nanoparticles (LNPs) were obtained after THF evaporated.

[0038] (5) Assembly of Janus nanopaper. The vacuum filtration method was used to assemble ODANF, LNPs and AZONF layer by layer to prepare Janus nanopaper with asymmetric wettability for oil-water separation. First, 10 ml of AZONF dispersion (0.2 wt%) was filtered through a PTFE polytetrafluoroethylene microporous membrane. Then, 0.5 mg·mL-1 of LNPs was deposited on top of AZONF. Finally, 20 mL of ODANF suspension (0.1 wt%) was deposited on top of LNP. After drying at 40 °C for 12 h, a wettability gradient composite membrane (JA / O@LNP) was obtained.

[0039] Example 2

[0040] The present invention provides a method for preparing gradient wettability self-cleaning nanopaper for oil-water separation. The invention uses amphiphilic lignin nanoparticles (LNPs) with a spherical topological structure as bridging particles and modified multi-scale cellulose as a heterogeneous substrate. A "hydrophilic-amphiphilic-hydrophobic" longitudinal fluid directional transport structure is formed under interfacial interaction. A light-induced antifouling Janus nanopaper with microchannel stability is prepared by a particle bridging strategy for oil-water separation.

[0041] The present invention relates to a method for preparing gradient wettability self-cleaning Janus nanopaper for oil-water separation, and the specific implementation process is as follows:

[0042] (1) Poplar cellulose with a moisture content of 25 wt% was ground using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC). After homogenization, 2 wt% nanocellulose (CNF) was obtained. CNF was anionized by TEMPO-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF).

[0043] (2) Preparation of hydrophobic fiber layer: 2 mg mL -1 EDS and NHS were added to the TOCNF dispersion at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 4 mg mL -1 The ODA was reacted at 60°C for 5 h. After the reaction, a hydrophobic cellulose derivative (ODANF) was obtained.

[0044] (3) Preparation of hydrophilic fiber layer: 2 mg mL -1 TOCNF was used as raw material, and EDS and NHS were added at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 0.3 mg mL -1 The AZO was reacted at 60°C for 5 h. After the reaction, a photoresponsive cellulose derivative (AZONF) was obtained.

[0045] (4) Preparation of lignin nanoparticles (LNPs): 20 mg of lignin was dissolved in 10 mL of tetrahydrofuran to obtain a concentration of 2 mg mL -1 The original lignin solution. At 500rmp·min -1 The original lignin solution was slowly added dropwise to 30 mL of ultrapure water at a rotation speed of 1.5 %. The mixture was stirred magnetically for 24 h, and lignin nanoparticles (LNPs) were obtained after THF evaporated.

[0046] (5) Assembly of Janus nanopaper: The vacuum filtration method was used to assemble ODANF, LNPs and AZONF layer by layer to prepare Janus nanopaper with asymmetric wettability for oil-water separation. First, 10 ml of AZONF dispersion (0.2 wt%) was filtered through a PTFE polytetrafluoroethylene microporous membrane. Then, 0.5 mg·mL-1 of LNPs was deposited on top of AZONF. Finally, 20 mL of ODANF suspension (0.1 wt%) was deposited on top of LNP. After drying at 40 °C for 12 h, a wettability gradient composite membrane (JA / O@LNP) was obtained.

[0047] Example 3

[0048] The present invention provides a method for preparing gradient wettability self-cleaning Janus nanopaper for oil-water separation. The invention uses amphiphilic lignin nanoparticles (LNPs) with a spherical topological structure as bridging particles and modified multi-scale cellulose as a heterogeneous substrate. A "hydrophilic-amphiphilic-hydrophobic" longitudinal fluid directional transport structure is formed under interfacial interaction. A light-induced antifouling Janus nanopaper with microchannel stability is prepared for oil-water separation through a particle bridging strategy.

[0049] The present invention relates to a method for preparing gradient wettability self-cleaning Janus nanopaper for oil-water separation, and the specific implementation process is as follows:

[0050] (1) Poplar cellulose with a moisture content of 25 wt% was ground using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC). After homogenization, 2 wt% nanocellulose (CNF) was obtained. CNF was anionized by TEMPO-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF).

[0051] (2) Preparation of hydrophobic fiber layer: 2 mg mL -1 EDS and NHS were added to the TOCNF dispersion at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 6 mg mL -1 The ODA was reacted at 60°C for 5 h. After the reaction, a hydrophobic cellulose derivative (ODANF) was obtained.

[0052] (3) Preparation of hydrophilic fiber layer: 2 mg mL -1 TOCNF was used as raw material, and EDS and NHS were added at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 0.6 mg mL -1 The AZO was reacted at 60°C for 5 h. After the reaction, a photoresponsive cellulose derivative (AZONF) was obtained.

[0053] (4) Preparation of lignin nanoparticles (LNPs): 40 mg of lignin was dissolved in 10 mL of tetrahydrofuran to obtain a concentration of 4 mg mL -1 The original lignin solution. At 500rmp·min -1 The original lignin solution was slowly added dropwise to 30 mL of ultrapure water at a rotation speed of 1.5 %. The mixture was stirred magnetically for 24 h, and lignin nanoparticles (LNPs) were obtained after THF evaporated.

[0054] (5) Assembly of Janus nanopaper: The vacuum filtration method was used to assemble ODANF, LNPs and AZONF layer by layer to prepare Janus nanopaper with asymmetric wettability for oil-water separation. First, 10 ml of AZONF dispersion (0.2 wt%) was filtered through a PTFE polytetrafluoroethylene microporous membrane. Then, 0.5 mg·mL-1 of LNPs was deposited on top of AZONF. Finally, 20 mL of ODANF suspension (0.1 wt%) was deposited on top of LNP. After drying at 40 °C for 12 h, a wettability gradient composite membrane (JA / O@LNP) was obtained.

[0055] Comparative Example 1:

[0056] (1) Poplar cellulose with a moisture content of 25 wt% was ground using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC). After homogenization, 2 wt% nanocellulose (CNF) was obtained. CNF was anionized by TEMPO-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF).

[0057] (2) Preparation of hydrophobic fiber layer: 2 mg mL -1 EDS and NHS were added to the TOCNF dispersion at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 6 mg mL -1 The ODA was reacted at 60°C for 5 h. After the reaction, a hydrophobic cellulose derivative (ODANF) was obtained.

[0058] (3) Preparation of hydrophobic monolayer separation membrane: 20 mL of 0.1 wt % ODANF suspension was prepared, and a hydrophobic monolayer separation membrane was prepared by vacuum filtration.

[0059] Comparative Example 2:

[0060] (1) Poplar cellulose with a moisture content of 25 wt% was ground using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC). After homogenization, 2 wt% nanocellulose (CNF) was obtained. CNF was anionized by TEMPO-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF).

[0061] (2) Preparation of hydrophilic fiber layer: 2 mg mL -1 TOCNF was used as raw material, and EDS and NHS were added at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 0.6 mg mL -1The AZO was reacted at 60°C for 5 h. After the reaction, a photoresponsive cellulose derivative (AZONF) was obtained.

[0062] (3) Preparation of hydrophilic monolayer separation membrane: 20 mL of 0.2 wt % AZONF suspension was prepared, and a hydrophobic monolayer separation membrane was prepared by vacuum filtration.

[0063] Comparative Example 3:

[0064] (1) Poplar cellulose with a moisture content of 25 wt% was ground using a 2500-II KRK high-concentration disc mill to obtain 5 wt% microfibrillated nanocellulose (MFC). After homogenization, 2 wt% nanocellulose (CNF) was obtained. CNF was anionized by TEMPO-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF).

[0065] (2) Preparation of hydrophobic fiber layer: 2 mg mL -1 EDS and NHS were added to the TOCNF dispersion at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 2 mg mL -1 The ODA was reacted at 60°C for 5 h. After the reaction, a hydrophobic cellulose derivative (ODANF) was obtained.

[0066] (3) Preparation of hydrophilic fiber layer: 2 mg mL -1 TOCNF was used as raw material, and EDS and NHS were added at a molar ratio of (1:1). Cellulose was activated for 1 h under magnetic stirring at 500 rpm. 0.3 mg mL -1 The AZO was reacted at 60°C for 5 h. After the reaction, a photoresponsive cellulose derivative (AZONF) was obtained.

[0067] (4) Preparation of Janus double-layer separation membrane: The Janus double-layer separation membrane was prepared by vacuum filtration method, and the ODANF and AZONF were assembled layer by layer in the order of layer 1. First, 10 ml of AZONF dispersion (0.2 wt%) was filtered through a PTFE polytetrafluoroethylene microporous membrane. Then, 20 mL of ODANF suspension (0.1 wt%) was deposited on top of the ODANF. After drying at 40 °C for 12 h, a wettability gradient composite membrane (JA / O) was obtained.

[0068] The separation efficiency and flux were determined as follows:

[0069] The prepared membrane was fixed between glass filter funnels, and 100 mL of oil-water layered mixture was passed through the filter device. The separation experiment was carried out under the action of water pump pressure (0.7 bar).1 ) is calculated using Formula 1:

[0070] η 1 =m / m 0 ×100% (1)

[0071] where m, m 0 They are respectively expressed as the mass of the permeated liquid before and after separation. In order to eliminate the influence of membrane adsorption, the separation efficiency is calculated after the initial separation.

[0072] In addition, the prepared membrane was fixed between glass filter funnels, and the volume of liquid passing through the membrane and the transmembrane pressure were recorded within 1 hour. The separation flux of the membrane was calculated by formula 2:

[0073] F=V / (A×t×P) (2)

[0074] Where F is the flux of the membrane, A(m 2 ) is the effective area of ​​the membrane (14.50 cm 2 ), t(h) is the test time, P(bar) is the pressure, V(L) is the volume of the separated phase. Each data point is the average of three parallel experiments.

[0075] Finally, it should be pointed out that the above embodiments are only representative examples of the present application. Obviously, the technical solution of the present application is not limited to the above embodiments, and there may be many variations. All variations that can be directly derived or associated with the contents disclosed in the present application by a person of ordinary skill in the art should be considered as the protection scope of the present application.

Claims

1. A method for preparing a gradient wettability self-cleaning nanopaper, characterized in that: The specific steps include: (1) Preparation of nanocellulose (CNF): Poplar wood cellulose with a moisture content of 20-30 wt% was ground and then homogenized to obtain 2 wt% nanocellulose; (2) anionizing the CNF prepared in step (1) through a tetramethylpiperidinyl oxide (TEMPO)-mediated oxidation reaction to obtain carboxylated nanocellulose (TOCNF); (3) Preparation of hydrophobic fiber layer: Take the TOCNF obtained in step (2) and prepare 1-3 mg·mL -1 dispersion, add EDS and NHS; stir to activate; add 2-10 mg·mL -1 ODA was reacted; after the reaction, a hydrophobic cellulose derivative (ODANF) was obtained; (4) Preparation of hydrophilic fiber layer: Take the TOCNF obtained in step (2) as raw material and prepare 2 mg mL -1 The dispersion was added with EDS and NH; stirred for activation; AZO was added for reaction; after the reaction, a photoresponsive cellulose derivative (AZONF) was obtained; (5) Preparation of lignin nanoparticles (LNPs): Dissolve lignin in tetrahydrofuran to obtain a concentration of 2-10 mg mL -1 The original solution of lignin; at 300-800rmp·min -1 At a rotation speed of , the original lignin solution is slowly added dropwise into ultrapure water; magnetic stirring is applied, and lignin nanoparticles are obtained after THF evaporates; (6) Assembly of Janus nanopaper: ODANF, AZONF and LNPs obtained in steps (3), (4) and (5) were set aside and assembled layer by layer in the order of ODANF, LNPs and AZONF using a vacuum filtration method to prepare Janus nanopaper with asymmetric wettability.

2. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 1, characterized in that: The step (1) specifically comprises grinding poplar cellulose with a water content of 25 wt% to obtain 5 wt% microfibrillated nanocellulose (MFC); and after a homogenization process, obtaining 2 wt% nanocellulose.

3. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 1, characterized in that: In the steps (2) and (3), the molar ratio of EDS and NHS added is (1:1).

4. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 1, characterized in that: The stirring activation in step (2) and step (3) is to activate cellulose for 1 hour under magnetic stirring at 500 rpm.

5. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 4, characterized in that: In step (3), 2-10 mg·mL of -1 The reaction was carried out with ODA at 60°C for 5h.

6. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 1, characterized in that: The step (4) of adding AZO to react is to add 0.1-0.9 mg·mL -1 The AZO was reacted at 60 °C for 5 h.

7. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 1, characterized in that: The step (5) is to dissolve 20-100 mg of lignin in 10 mL of tetrahydrofuran to obtain a concentration of 2-10 mg mL -1 The original lignin solution; at 500rmp·min -1 The original lignin solution was slowly added dropwise into 30 mL of ultrapure water at a rotation speed of ; magnetic stirring was performed for 24 h, and lignin nanoparticles were obtained after THF evaporated.

8. The method for preparing the gradient wettability self-cleaning nanopaper according to claim 1, characterized in that: The step (6) is specifically as follows: first, 10 ml of AZONF dispersion (0.2 wt%) is filtered through a PTFE polytetrafluoroethylene microporous membrane; then, 0.5 mg·mL-1 of LNPs is deposited on top of AZONF; finally, 20 mL of ODANF suspension (0.1 wt%) is deposited on top of LNP; after drying at 40° C. for 12 h, a wettability gradient composite membrane (JA / O@LNP) is obtained; wherein the hydrophobic layer is recorded as the JO layer, and the hydrophilic layer is recorded as the JA layer.

9. A gradient wettability self-cleaning nanopaper, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the gradient wettability self-cleaning nanopaper according to claim 9 in oil-water separation.

Citation Information

Patent Citations

  • Super-hydrophobic modification method of nanocellulose

    CN113773404A

  • Preparation method and application of aminated wood aerogel for adsorbing heavy metals in water

    CN114832801A

  • Janus type micro-nano composite fiber membrane with super-hydrophobic single surface and super-hydrophilic single surface and preparation method of Janus type micro-nano composite fiber membrane

    CN115418795A

  • Janus composite for oil in water separation

    US20230212037A1